Implementasi Sistem Akuntansi Berbasis Teknologi untuk Meningkatkan Transparansi dan Pengelolaan Keuangan Koperasi - Ahmad Bukhori Muslim; Dian Sulistyorini Wulandari; Kuwat Riyanto; Yohanes Bosco Riando (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Implementing technology-based accounting systems in cooperatives aims to enhance transparency and efficiency in financial management. This initiative involves intensive mentoring of cooperative members in adopting new technologies for transaction recording, financial reporting, and real-time cash flow management. The results of this implementation show significant improvements in the member's ability to use accounting systems, strengthening financial transparency and facilitating strategic decision-making. Despite challenges such as resistance to change and the availability of adequate technological infrastructure, the program has successfully delivered positive impacts that can assist cooperatives in improving service quality to members and strengthening their financial position in the market. With ongoing support and the development of more specific training modules, this technology implementation is expected to continue to provide long-term benefits for cooperatives and their members.